Online personal computer component customization / Mohamad Aminuddin Mohd Bayaki - Mohd Bayaki, Mohamad Aminuddin (2014)
Customization is one of the vital elements to the success of e-commerce. The research on the concept of customization has emerged rapidly due to the need of understanding it in order to improve current and future e-commerce implementation. The lack of component’s customization on the personal computer is one of the focused issues among its buyer. This project aims to develop an e-commerce website that sell personal computer’s component that enable the customer to customize the component to be a complete personal computer. Thus, it will increase the satisfaction among customers. The project examines the main component part for customizing, reviewing several customization related technique, mechanisms and technology proposed and recommended by other scholar. This e-commerce website is developed by following structured analysis methodology which comprises of Planning Phase, Analysis Phase, Design Phase, Implementation Phase, Testing Phase and Documentation Phase. The evaluation of the e-commerce website has been done which focuses on the user interface and usability of the system. Based on the evaluation result, it showed that the user interface and usability of the system satisfy the target user. However, the system still needs to be improved in the future to make it more effective, interactive and more usable.